Prospective, Controlled, Multicentre Study of Loperimide in Pregnancy. (1st May 2000) - Einarson, A; Mastroiacovo, P; Arnon, J; Ornoy, A; Addis, A; Malm, H; Koren, G
Abstract : BACKGROUND: Loperamide is a synthetic piperidine derivative used for the treatment of both acute and chronic diarrhea. Little is known about its safety and risk in pregnancy. Human data are limited to one surveillance study of Michigan Medicaid patients, with 108 women exposed in the first trimester. In this study there were six major birth defects, three of which were cardiovascular anomalies. OBJECTIVES: To determine whether loperamide use in pregnancy is associated with an increased risk of major malformations. The secondary end points were rates of minor malformations, spontaneous and therapeutic abortions, and premature births, and mean birth weights. PATIENTS AND METHODS: Women counselled by five teratogen information centres on the safety and risk of loperamide in pregnancy were followed after delivery and compared with a similar group of women matched for age, smoking, alcohol and other exposures. RESULTS: One hundred and five follow-ups were completed; 89 of the women were exposed to loperamide in the first trimester of pregnancy. There were no statistically significant differences between the study group and the control group in any of the end points that were analyzed. However, of women who took loperamide throughout their pregnancy, 21 of 105 had babies who were 200 g smaller than babies in the control group. CONCLUSIONS: The results of this study suggest that the use of loperamide during pregnancy is not associated with an increased risk of major malformations.